Galton 2012: the bibliometric journey continues - Gorraiz, Juan; Gumpenberger, Christian; Wieland, Martin (Qualitative and Quantitative Methods in Libraries, 2017)
Francis Galton was not only a universal genius; he can also be regarded as a scientometric pioneer. On the occasion of his 100th death anniversary in 2011, he was used as a role model for a bibliometric impact analysis of his works. This is the followup study of a previous citation analysis, which was now expanded by introducing ProQuest Dissertations & Theses (PQDT) as a complementary data source. Additionally all retrieved documents in WoS either citing or mentioning Galton were visualized using Bibexcel, Pajek and VOS Viewer. Furthermore Galton‟s h-index and g-index were calculated and found to be very high compared to other historic scientific personalities. The citation-to-obliteration ratio was different for PQDT in comparison to WoS or Scopus. Visualization allows better interpretation and understanding of the obtained results and is useful for the identification of eponyms.  Overall citation analysis and occurrence counting are complementary useful methods for the impact analysis of the works of “giants”. This type of retrospective bibliometric studies presents an interesting and promising field of activity for librarians and information specialists.